The efficacy of ATP removal on gym contact surfaces with disinfectant wipes - Tam, Victor; BCIT School of Health Sciences, Environmental Health; Sidhu, Bobby (BCIT Environmental Public Health Journal, 2014)
Background: Gym equipment surfaces are known to harbor a range of contaminants due to the wide range of community use of the equipment. Certain gym equipment undergoes daily sanitation, however many other equipment surfaces do not. This study measures the levels of contamination on certain gym equipment surfaces at an educational institute gym facility and determines the contamination levels after disinfectant wipes are applied. Methods: The method to obtain the data was determined by the use of the Hygiena Systemsure II ATP analyzer in conjunction with Hygiena Ultrasnap ATP surface swabs. Gym equipment (barbells, dumbbells, machine handles, cable attachments) and other surfaces (benches, floor mats) were swabbed subsequently after a random gym patron had used the equipment to capture an accurate representation of the cleanliness of the surfaces. Disinfectant wipes were then applied to the same area before being swabbed again to determine contamination levels after disinfection. Results: The results demonstrated a statistically significant difference in the reduction of ATP levels with the use of disinfectant wipes with a p-value of 0.00001 at α=0.05. Alpha error was highly unlikely with a p-value being that low. Power was 99.9%, therefore there is a strong likelihood that we are correctly rejecting the null hypothesis. Conclusion: The study can conclude that disinfectant wipes do make a significant difference in surface cleanliness levels. Equipment that does not undergo routine cleaning such as the equipment used by the hands carry a much higher contamination rate than the body contact surfaces. Gym patrons should disinfect all body contact surfaces prior to use to reduce the risk of getting an infectious disease.